2017
DOI: 10.1103/physrevfluids.2.024602
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of turbulent heat transfer in an annulus at supercritical pressure

Abstract: Heat transfer to fluids at supercritical pressure is different from heat transfer at lower pressures due to strong variations of the thermophysical properties with the temperature. We present and analyze results of direct numerical simulations of heat transfer to turbulent CO 2 at 8 MPa in an annulus. Periodic streamwise conditions are imposed so that mean streamwise acceleration due to variations in the density does not occur. The inner wall of the annulus is kept at a temperature of 323 K, while the outer wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The factors α A h , α Ac , c h and c c suggest that the contribution of the hot part to the Nusselt number is different from the contribution by the cold part. In a previous publication, we found evidence that this is indeed the case [18]. Equation ( 16) depends on P r h ≡ P r(T h ) and P r c ≡ P r(T c ).…”
Section: Creating a Relationsupporting
confidence: 60%
See 1 more Smart Citation
“…The factors α A h , α Ac , c h and c c suggest that the contribution of the hot part to the Nusselt number is different from the contribution by the cold part. In a previous publication, we found evidence that this is indeed the case [18]. Equation ( 16) depends on P r h ≡ P r(T h ) and P r c ≡ P r(T c ).…”
Section: Creating a Relationsupporting
confidence: 60%
“…In this paper, we present a new heat transfer model, which is based on our observations of direct numerical simulations of heated turbulent flows at supercritical fluids [18]. This model takes variable thermal conductivity, and specific heat capacity into account.…”
Section: Introductionmentioning
confidence: 99%
“…One dimensional rarefraction properties in compression shocks have been investigated recently by [ 12 ] for non-ideal gases close to the vapour-liquid critical point. [ 13 ] also investigates the heat transfer characteristics in fully developed turbulent flows of CO 2 in an annular geometry by simulating the low-Mach number approximation Navier-Stokes equations. In many previous works, such as [ 4 , 7 , 9 ] and [ 13 ], Navier-Stokes equations have been solved using the low-Mach number approximation, which takes into account changes in density due to changes in temperature, but ignores the effect of density changes due to the pressure variations.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] also investigates the heat transfer characteristics in fully developed turbulent flows of CO 2 in an annular geometry by simulating the low-Mach number approximation Navier-Stokes equations. In many previous works, such as [ 4 , 7 , 9 ] and [ 13 ], Navier-Stokes equations have been solved using the low-Mach number approximation, which takes into account changes in density due to changes in temperature, but ignores the effect of density changes due to the pressure variations. In order to further improve our understanding of the fluid dynamics of supercritical fluids and also to capture the compressibility effects, a fully compressible Navier-Stokes solver has been developed, which can include the effects of density changes due to the variation of both pressure and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up study (Peeters et al. 2017), the authors further analysed the data on the annular flow, specifically focusing on the behaviours of turbulent heat transfer under the influences of the variations of thermal properties. Based on the analyses of the budget of the turbulent heat transfer and quadrant analyses, the authors concluded that both the fluctuations and the mean gradients of the density and molecular Prandtl number had a significant influence on the turbulent heat flux.…”
Section: Introductionmentioning
confidence: 99%